2015
DOI: 10.1016/j.ejcdt.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The use of multi-detector computed tomography and ultrasonography for evaluation of pleural lesions

Abstract: Background and objective: Multidetector CT (MDCT) and ultrasonography (US) are of increasing importance for assessment of many pulmonary disorders. Our aim was to evaluate their role in diagnosis of pleural diseases.Methods: Patients from Tanta University Hospital who were suspected to have pleural lesions (symptoms, signs and/or suggestive chest X-ray) during one year period were enrolled in the study. US and MDCT were done for all of them, then data were reported and analyzed.Results: Seventy-one patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Previous studies also reported that ultrasound detected 70% of cases pleural thickness but chest radiography detected only 10% [17] . Helala et al study showed that ultrasound detects pleural thickness more accurate than chest radiography [18] .…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies also reported that ultrasound detected 70% of cases pleural thickness but chest radiography detected only 10% [17] . Helala et al study showed that ultrasound detects pleural thickness more accurate than chest radiography [18] .…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, Bediwy et al, (7) stated that in TUS was less sensitive than CT chest in detecting pleural thickening and pleural nodules or masses. Also Raj et al, (9) who stated that CT chest allows detailed evaluation of the pleura and differentiation of benign from malignant pleural disease and also adequate enhancement of the pleura enables differentiation of the thickened pleura from adjacent effusion or aerated or collapsed lung.…”
Section: Resultsmentioning
confidence: 99%
“…Bediwy et al, (7) stated that in TUS diagnosed 83.3% of free pleural effusion lesions, 60% of encysted pleural effusion lesions with diagnosing all empyema lesions, but less sensitive in detecting pleural thickening and pleural nodules or masses.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Bediwy et al, (12) stated that in TUS was less sensitive than CT chest in detecting pleural thickening and pleural nodules or masses. Also Raj et al, (16) who stated that CT chest allows detailed evaluation of the pleura and differentiation of benign from malignant pleural disease and also adequate enhancement of the pleura enables differentiation of the thickened pleura from adjacent effusion or aerated or collapsed lung.…”
Section: Discussionmentioning
confidence: 99%
“…Bediwy et al, (12) stated that in TUS diagnosed 83.3% of free pleural effusion lesions, 60% of encysted pleural effusion lesions with diagnosing all empyema lesions, but less sensitive in detecting pleural thickening and pleural nodules or masses. Sikora et al, (13) also reported that transthoracic US serves as a more accurate imaging tool than chest radiography in the diagnosis of pleural effusions and allows discrimination of pleural effusions from other lung pathology which may appear similar on a chest X-ray.…”
Section: Discussionmentioning
confidence: 99%